ChemInform Abstract: Alkyl—Aryl Ketone Synthesis via Nickel‐Catalyzed Reductive Coupling of Alkyl Halides with Aryl Acids and Anhydrides. Issue 42 (October 2015) - Jia, Xiao; Zhang, Xinghua; Qian, Qun; Gong, Hegui
Abstract A series of ketones (III) and (V) is readily prepared by a Ni‐catalyzed reductive coupling of halides (I) and (IV) with aryl acids (II).